Naked-eye and ratiometric fluorescence probe for fast and sensitive detection of hydrogen sulfide and its application in bioimaging. (8th November 2018) - Ma, Jianlong; Li, Feifei; Li, Qiang; Li, Yijing; Yan, Chaoxian; Lu, Xiaofeng; Guo, Yong
Abstract : A sensitive and ultrafast ratiometric fluorescence probe for the detection of hydrogen sulfide (H2 S) in HeLa cells and zebrafish. Abstract : Hydrogen sulfide (H2 S) is a remarkable endogenous gasotransmitter involved in numerous biological processes, and its noninvasive, rapid and accurate measurement in living cells and animals is urgently needed. Herein, we report a ratiometric fluorescent H2 S-specific probe (CyT ). This new probe can be readily prepared by modifying the triflate group (CF3 SO3 − ) into hemicyanine, and it shows excellent sensing properties. First, CyT is highly selective against other biologically relevant anions, cations, reactive sulfur and small molecules; meanwhile, it has a low limit of detection (LOD) to H2 S (7.33 nM) In addition, CyT exhibits rapid response to H2 S (rate constant is 1464 M −1 s −1 ) and apparent color change from dark blue to very pale green, which is observed with the naked-eye. Furthermore, it exhibits low cytotoxicity to HeLa cells and can be successfully used for the detection of H2 S activity in cells and zebrafish.